Spontaneous and induced labor: association with maternal well-being three months after childbirth. Issue 4 (21st April 2022) - Ponti, Lucia; Ghinassi, Simon; Tani, Franca
ABSTRACT: A woman's first childbirth represents a moment of elevated maternal emotional vulnerability. Indeed, there is a prevalence of anxiety and depression symptomatology in primiparas during the postpartum period that negatively influences the well-being of the woman, of her newborn, and of the quality of their attachment bond. Much attention has been paid to the possible risk factors involved in the onset of mood disturbance in the postpartum. However, knowledge is still limited regarding the role played by the specific clinical aspects linked to labor. Therefore, the aim of the present study was to explore whether spontaneous or elective induction labor is linked to the level of postnatal depression and anxiety three months after birth. One hundred and sixty-one women (Mage = 31.63; SD = 4.88) were recruited, using the following inclusion criteria: native Italian women; age > 18 years; physically and psychologically healthy nulliparous with singleton no-risk pregnancy; no previous abortion or interruption of pregnancy; no previous psychopathological diagnoses. Exclusion criteria: twin pregnancy, fetal pathologies, and planned elective cesarean. Data was collected at two different times: T1 (day of childbirth) clinical data of labor (spontaneous or induced) from hospital records; T2 (three months after birth) level of mother's depression and anxiety. In order to explore if the level of depression and anxiety three months after childbirth differ in women according to the type of labor, spontaneous or induced, two univariate analyses of variance (ANOVA) were conducted. Results showed that women who had a spontaneous labor reported lower levels of anxiety and depression than women who had an induced labor. Our results highlight the significant implications that the mode of labor has on the emotional well-being of mothers, underlining the need to support women throughout all their transition to motherhood, including the childbirth experience.